2021
DOI: 10.1002/saj2.20257
|View full text |Cite
|
Sign up to set email alerts
|

Do soil carbon sequestration and soil fertility increase by including a gramineous cover crop in continuous soybean?

Abstract: Cover cropping is a farming practice that may improve C sequestration and soil fertility, but these effects can vary under different edaphoclimatic conditions. The effects of including a winter gramineous cover crop (CC) in continuous soybeans were evaluated in three long-term experiments (8 yr) on one coarse-textured soil and two finetextured soils in the Pampas region of Argentina. The impacts of CC on soil C sequestration, soil nutrient availability, soil organic C (SOC), and N contents of soil particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
1
10
0
6
Order By: Relevance
“…On the other hand, SOC values at both sites were similar with other studies under similar soil texture and climates (Steenwerth et al, 2010;Wolff et al, 2018;Yu et al, 2019). However, the lack of strong effects of tillage on SOC at the Fresno County vineyard can be attributed to the significantly less SOM with more sandy soil texture in the Fresno County vineyard compared to the Napa County vineyard with finer soil texture, which could have possibly led to excessive aeration and permeability in the soil (Yu et al, 2019;Beltrań et al, 2021), hence a very low SOM baseline for the Fresno site. As for the Napa site with CT significantly deducing soil SOC, there has been recent work in the similar Mediterranean climates that is generally in agreement with these observations, reporting increased SOC accumulation under minimum and complete lack of tillage (Loṕez-Bellido et al, 2010;Wolff et al, 2018).…”
Section: Estimates Of Net Carbon Balance At the Grapevine And Vineyar...supporting
confidence: 82%
“…On the other hand, SOC values at both sites were similar with other studies under similar soil texture and climates (Steenwerth et al, 2010;Wolff et al, 2018;Yu et al, 2019). However, the lack of strong effects of tillage on SOC at the Fresno County vineyard can be attributed to the significantly less SOM with more sandy soil texture in the Fresno County vineyard compared to the Napa County vineyard with finer soil texture, which could have possibly led to excessive aeration and permeability in the soil (Yu et al, 2019;Beltrań et al, 2021), hence a very low SOM baseline for the Fresno site. As for the Napa site with CT significantly deducing soil SOC, there has been recent work in the similar Mediterranean climates that is generally in agreement with these observations, reporting increased SOC accumulation under minimum and complete lack of tillage (Loṕez-Bellido et al, 2010;Wolff et al, 2018).…”
Section: Estimates Of Net Carbon Balance At the Grapevine And Vineyar...supporting
confidence: 82%
“…It has indeed been shown that using a diverse pool of cover crops provides multiple scenarios for manipulating on‐farm diversity to enhance multiple ecosystem functions beyond just crop yield (Clark, 2008; Islam & Sherman, 2021). For instance, leguminous cover crops with high nitrogen content enhance soil nitrogen availability, while gramineous cover crops equipped with dense root systems may promote C sequestration (Beltrán et al, 2021; Sharma et al, 2018). Moreover, given the wide range of possible cover crop species and the great variety in their functional traits, making use of diverse cover crops may further contribute to multiple benefits, including higher soil resource availability and crop yield, as well as promoting soil health (Carlson & Stockwell, 2013; Schipanski et al, 2014; Wood & Bowman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Barthès et al (2008) reported that sesquioxides had more important aggregating role than SOM in tropical soils from sub-Saharan Africa and Brazil. In this study, although we did not measure sesquioxides, the available Fe, Mn, Cu, and Zn were increased after 17 yr of application of biological measures (Figure 3), implying the release of these elements from sesquioxides (Beltrán et al, 2021;Eneji et al, 2003) and thus a decrease of sesquioxides, which may lead to a decrease in soil particle aggregation.…”
Section: Soil Physicochemical Properties Under Different Conservation...mentioning
confidence: 68%
“…In this study, the orchards with biological measures had higher available micronutrients than that with traditional clean‐tillage. The higher available Cu and Zn might be attributed to the increased SOM activating these elements by forming stable complexes with metal ions, thereby increasing their availability (Beltrán et al., 2021). This explanation is also supported by the positive relationship between SOM and available micronutrients (Figure 4) (Ray et al., 2021).…”
Section: Discussionmentioning
confidence: 99%